ANALISIS RESIKO KERJA DAN UPAYA PENGENDALIAN BAHAYA PADA DINAS SATPOL PP DAN PETUGAS PEMADAM KEBAKARAN KABUPATEN KERINCI: AFRIYANTI - AFRIANTI, SE., M.Pd (LPPM STIA Nusantara Sakti, 2023)
Work Risk Analysis and Hazard Control Efforts at the Satpol Pp Service and Kerinci District Fire Officers. The phenomenon that occurs in Kerinci Regency when a fire occurs, firefighters often complain of this because the equipment and equipment owned by the Kerinci District Fire Service can be said to be classified as very limited and this can result in firefighters having a greater risk on their way and when being at the fire site As a result, fire incidents are often fatal and recurrent. When carrying out their duties in extinguishing operations, the safety of firefighters should receive serious attention due to electricity, heat, fire, working at heights, extinguishing equipment, explosions, backdraft and flashover, burning conditions of buildings, sharp objects, or physical clashes with residents.The research method used is qualitative, the data source in this study were 9 people. The implementation of control of work risks and hazards for firefighters is carried out in the area of ??Kerinci district which is the object of research, in terms of reducing the risks and dangers of firefighters by increasing the quality and awareness of firefighters, this can be done by providing incentives equivalent to firefighters In addition to these fires, the fire department must have complete equipment and equipment in order to reduce risks while working.